THE HISTORY OF ETHNOCONFESSIONAL DEVELOPMENT OF THE REPUBLIC OF KAZAKHSTAN - Bekmagambetova, M.; Bekmagambetov, R. (PUBLISHINGS of Kostanay State Pedagogical University, 2018)
The article reviews the history of ethno-confessional development of Kazakhstan from the moment of gaining its independence to the present. There are 130 ethnoses and over four thousand religious associations in the country. Kazakhstan has unique experience of preservation of national and cultural values of all people. The Kazakhstan model of interethnic tolerance was built on the basis of constructive creative interaction of ethnocultural associations and the state.
Keywords: ethnos; confession; tolerance; consent; patriotism; the Doctrine of national unity; Assembly of People of Kazakhstan; ethnocultural education